Effects of Relay Cropping of Corn on the Productivity and Quality of Flue‐Cured Tobacco. (1st September 2014) - Zhou, Guisu; Yin, Xinhua; Li, Yongmei; Yang, Huanwen; Zhao, Zhengxiong; Che, Peikuan; Cao, Qizhang; Zhao, Hong; Wang, YongJie; Xu, Lei
Abstract : Relay cropping timing has been frequently reported to influence flue‐cured tobacco ( Nicotiana tabacum L.) production. However, the optimal planting time for a relay corn ( Zea mays L.) crop on flue‐cured tobacco fields is unknown in terms of tobacco health, yield, quality, and economic value. A field experiment was conducted with 10, 17, 24, and 31 d after flue‐cured tobacco apex excision as the relay cropping timings of corn, and tobacco monoculture as the control at Chuxiong, Yunnan, China in 2010 and 2011. The five treatments were repeated three times in a randomized complete block design. The occurrence of brown spot ( Alternaria alternata ), plant biomass, plant N and K nutrition, yield, chemical composition, smoking quality, and economic value of flue‐cured tobacco were affected by year. Relay cropping 17 d after tobacco apex excision resulted in better chemical composition and smoking quality. The incidence and severity index of brown spot, plant biomass, plant N and K nutrition, yield, chemical composition, smoking quality, and economic value of tobacco were not significantly affected by the relay cropping timing of corn, indicating that relay cropping of corn at a later growth stage of flue‐cured tobacco has no negative effect on tobacco production while the relay corn crop may bring additional income to tobacco growers. In conclusion, if the production of relay corn is profitable, relay cropping of corn after flue‐cured tobacco apex excision could become a recommended cropping system in Yunnan and other regions with similar environmental conditions.